Overtourism Phenomenon at Borobudur Temple Based on The Penta Helix Perspectives - Ersya Fadilla Rachmat; Sutono, Anang; Renalmon Hutahaean (Politeknik Pariwisata NHI Bandung, 2021)
The purpose of this research is to identify the overtourism issues at Borobudur Temple based on Penta Helix's perspectives. There is 5 kind of issues that will be identified based on Peeter et al (2018) such as issues related to tourist number, issues related to physical or build environment, socio-cultural issues, socio-economic issues and tourist perception based on Penta Helix perspectives. The empirical condition happened that many events like Borobudur Symphony, Concert Marathon, and the liked conducted in the area of Borobudur Temple. This study used qualitative research. Researchers wanted to understand the phenomena of certain social conditions that occurred in the research place. To identify the overtourism phenomenon in destination, the interview was conducted with each stakeholder according to Penta Helix elements which consist of academicians, business, community, government, and media. By interviewing each of Penta Helix elements, comprehensive findings can be produced following the 5 kinds of issues mentioned. According to each stakeholder by the Penta Helix model, there are some overtourism phenomena or issues that already happened in the destination. Those are issues related to tourist numbers, physical and built environment, socio-cultural issues, and tourist perception. And one of the issues that have not happened in the destination is socio-economic issues.